The Current State and the Peculiarities of Physical Activity of Teenagers in Ukraine and Poland - Solovei, Alla; Rymar, Olha; Yaroshyk, Marta; Sorokolit, Nataliya; Соловей, Алла; Римар, Ольга; Ярошик, Марта; Сороколіт, Наталія (Східноєвропейський національний університет ім. Лесі Українки, 2017)
Thematic justification is determined by searching for ways to optimize the level of human physical activity. Studying the level of physical activity of residents of neighboring countries of Ukraine and Poland, which have differences in systems of education, culture, socio–economic structure, will assist in searching for ways to optimize the level of physical activity of the population of both countries. Special focus of the study will be on the problem of studying physical activity of children and youth, the proper level of which is a guarantee of nation’s health. Research objective is to establish the current state and characteristics of physical activity of 13–15–year–old children living in Poland and Ukraine. Research results. The article provides a comparative analysis of the results of a survey of Polish and Ukrainian 13–15–year–old school students. A comparative analysis of indicators of physical activity of 13–15–year–old children living in Poland and Ukraine was also conducted. It has been established that children of both countries equally prefer sedentary activities in their spare time. Ukrainian school students give a higher evaluation to physical education classes and their own level of physical aptitude. At the same time, there is a tendency among Ukrainian school students towards the decrease of the level of physical activity from 13 to 15 years of age if compared to Polish school students. Conclusions: obtained pedometer indicators are below normal, which is indicative of a sedentary lifestyle of students of this age group (Ukrainian students – 7,9 thousand steps per day, Polish students – 9,7 thousand steps per day). Polish students have a tendency towards increasing the volume of physical activity (13 years old – 8,8 thousand steps per day, 15 years old – 11 thousand steps per day). Conversely, students in Ukraine tend to decrease the volume of physical activity (13 years – 9,9 thousand steps per day, 15 years – 6,7 thousand steps per day). Актуальність дослідження зумовлена пошуком способів оптимізації рівня рухової активності людини. Вивчення рівня рухової активності мешканців сусідніх держав України та Польщі, які мають відмінності в системах освіти, культури, соціально–економічного устрою, дасть змогу полегшити пошук шляхів оптимізації рівня рухової активності населення обох країн. У дослідженні особливу увагу приділено проблемі вивчення рухової активності дітей і молоді, належний рівень якої є гарантією здоров’я нації. Мета дослідження – установити сучасний стан та особливості рухової активності дітей 13–15 років, котрі проживають у Польщі й Україні. Результати дослідження. У статті представлено порівняльний аналіз результатів анкетування польських та українських школярів 13–15 років. Також проведено порівняльний аналіз показників рухової активності дітей 13–15 років України й Польщі. Установлено, що діти обох країн однаково надають перевагу малорухливим видам діяльності у вільний час. Українські школярі вище оцінюють урок фізичного виховання і власний рівень фізичної підготовленості. Водночас в українських учнів простежено тенденцію до зниження рівня рухової активності з 13 до 15 років, порівняно з польськими школярами. Висновки. Отримані показники крокометрії є нижчими за норму, що свідчить про малорухливий спосіб життя учнів цієї вікової групи (українські діти – 7, 9 тис. кроків на день; польські – 9,7 тис.). В учнів Польщі спостерігаємо тенденцію до збільшення обсягу рухової активності (13 років – 8,8 тис. кроків на день; 15 років – 11 тис.). І навпаки, у школярів України простежено тенденцію до зниження обсягу рухової активності (13 років – 9,9 тис. кроків на день; 15 років – 6,7 тис.).
Сучасний стан та особливості рухової активності підлітків України й Польщі.
Keywords: physical activity; children; school students; Ukraine; Poland; рухова активність; діти; школярі; Україна; Польща